Implementation and Operational Research: Effect of Integration of HIV Care and Treatment Into Antenatal Care Clinics on Mother-to-Child HIV Transmission and Maternal Outcomes in Nyanza, Kenya. (15th August 2015) - Washington, Sierra; Owuor, Kevin; Turan, Janet M.; Steinfeld, Rachel L.; Onono, Maricianah; Shade, Starley B.; Bukusi, Elizabeth A.; Ackers, Marta L.; Cohen, Craig R.
Abstract : Background: Many HIV-infected pregnant women identified during antenatal care (ANC) do not enroll in long-term HIV care, resulting in deterioration of maternal health and continued risk of HIV transmission to infants. Methods: We performed a cluster randomized trial to evaluate the effect of integrating HIV care into ANC clinics in rural Kenya. Twelve facilities were randomized to provide either integrated services (ANC, prevention of mother-to-child transmission, and HIV care delivered in the ANC clinic; n = 6 intervention facilities) or standard ANC services (including prevention of mother-to-child transmission and referral to a separate clinic for HIV care; n = 6 control facilities). Results: There were high patient attrition rates over the course of this study. Among study participants who enrolled in HIV care, there was 12-month follow-up data for 256 of 611 (41.8%) women and postpartum data for only 325 of 1172 (28%) women. By 9 months of age, 382 of 568 (67.3%) infants at intervention sites and 338 of 594 (57.0%) at control sites had tested for HIV [odds ratio (OR) 1.45, 95% confidence interval (CI): 0.71 to 2.82]; 7.3% of infants tested HIV positive at intervention sites compared with 8.0% of infants at control sites (OR 0.89, 95% CI: 0.56 to 1.43). The composite clinical/immunologic progression into AIDS was similar in both arms (4.9% vs. 5.1%, OR 0.83, 95% CI: 0.41 to 1.68). Conclusions: Despite the provision of integrated services, patient attrition was substantial in both arms, suggesting barriers beyond lack of service integration. Integration of HIV services into the ANC clinic was not associated with a reduced risk of HIV transmission to infants and did not appear to affect short-term maternal health outcomes. Abstract : Supplemental Digital Content is Available in the Text.